NILAI HERITABILITAS DAN KORELASI GENETIK SIFAT PERTUMBUHAN DARI SILANGAN AYAM LOKAL DENGAN AYAM BANGKOK - Soeroso Soeroso; Yulius Duma; Selvy Mozin (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The research conducted to estimate the heritability value and genetic correlation of growth traits of crossbred F (indigenous hens X Bangkok cocks) were done over 28 weeks. Five groups of pen mating poultry were used in which one cock and five hens were used for each group. Therefore, there were 5 cocks and 25 hens as parent stock and 152 crossbred F. Variables of the research were body weight of DOC, body weight of 4th weeks and 8th weeks. The variations of body weight by sex were eliminated by transforming the female body weight to male body weight using correction factor. Estimation of heritability value (h²) used an anova of nested design method. Estimation of genetics correlation (rG) used an  ancova of nested design. Results of heritability estimates and genetic correlation showed that the h² was 0.13 for Doc body weight, 0. 67 for 4th weeks, and 0,59 8th weeks. The rG was 0.89 for DOC to 4th week body weight, and 0.55 for DOC to 8th week body weight